Automated Folding of Origami Lattices: From Nanopatterned Sheets to Stiff Meta‐Biomaterials (Small 3/2023). Issue 3 (18th January 2023) - van Manen, Teunis; Ganjian, Mahya; Modaresifar, Khashayar; Fratila‐Apachitei, Lidy E.; Zadpoor, Amir A.
Abstract : Origami Lattices Folding of flat sheets into 3D structures is a promising approach for the fabrication of functionalized metamaterials. Inspired by sheet metal forming, Teunis van Manen and co‐workers in article number 2203603 develop an automated folding method for the folding of stiff lattice structures comprising large numbers of small interconnected unit‐cells. Surface nano‐features are applied at the initial flat material and preserved during the process of folding.